2022
DOI: 10.1002/biof.1816
|View full text |Cite
|
Sign up to set email alerts
|

Altered triglyceride glucose index and fasted serum triglyceride high‐density lipoprotein cholesterol ratio predict incidence of cardiovascular disease in the Mashhad cohort study

Abstract: The triglyceride glucose (TyG) index and triglyceride/high lipoprotein density cholesterol (TG/HDL‐C) are two important risk markers to evaluate the insulin resistance and cardiovascular diseases (CVDs). To assess the association between TG/HDL‐C and TyG index and CVDs. The Mashhad stroke and heart association disorder cohort study started in 2010 and has been continued until 2020. During 6‐year follow‐up of 9704 participants, 235 events including 118 acute coronary syndrome (ACS), 83 chronic coronary syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In addition, one retrospective cohort study showed that the TyG index was associated with increased CVD incidence in a nondiabetes population after a median follow-up of 5.6 years [ 35 ]. Another prospective cohort study confirmed this association (per 1 SD HR = 1.82; 95% CI 1.38–2.40) after excluding patients with diabetes and CVD history after 6 years of follow-up [ 39 ]. Park demonstrated the relevance of CAD incidence for the TyG index in a nondiabetes population (HR = 2.28; 95% CI 1.69–2.40) [ 40 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, one retrospective cohort study showed that the TyG index was associated with increased CVD incidence in a nondiabetes population after a median follow-up of 5.6 years [ 35 ]. Another prospective cohort study confirmed this association (per 1 SD HR = 1.82; 95% CI 1.38–2.40) after excluding patients with diabetes and CVD history after 6 years of follow-up [ 39 ]. Park demonstrated the relevance of CAD incidence for the TyG index in a nondiabetes population (HR = 2.28; 95% CI 1.69–2.40) [ 40 ].…”
Section: Discussionmentioning
confidence: 84%
“…The span of follow-up ranged from 4.1 years to 16.1 years. Of these studies, ten studies were performed in Asia (four in China [ 19 , 20 , 37 , 38 ], four in Korea [ 34 – 36 , 40 ] and two in Iran [ 18 , 39 ]), one was from the Americas (The United States of America [USA] [ 42 ]) and one was from Europe (Spain [ 41 ]). In addition, six were prospective cohort studies [ 18 – 20 , 39 41 ]; the others were retrospective cohort studies [ 34 38 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WHtR has been reported to be a better discriminator of CHD and stroke risk than WC and BMI [61][62][63]. The TG/HDL-C ratio is likewise considered a decent indicator of CVD risk [64,65]. The TG/HDL-C ratio has been shown to reflect small atherogenic LDL-C particles and is strongly associated with IR and metabolic syndrome [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…The TG/HDL-C ratio is likewise considered a decent indicator of CVD risk [64,65]. The TG/HDL-C ratio has been shown to reflect small atherogenic LDL-C particles and is strongly associated with IR and metabolic syndrome [65][66][67]. Metabolic syndrome and IR are well-known markers of CVD risk, especially diabetes, hypertension, hyperlipidemia, and atherosclerosis [68,69].…”
Section: Discussionmentioning
confidence: 99%